Autotransporter MisL of Salmonella enterica serotype Typhimurium facilitates bacterial aggregation and biofilm formation. Issue 17 (12th June 2018) - Wang, Shaohui; Yang, Denghui; Wu, Xiaojun; Wang, Yang; Wang, Dong; Tian, Mingxing; Li, Tao; Qi, Jingjing; Wang, Xiaolan; Ding, Chan; Yu, Shengqing
Abstract: Salmonella enterica serovar Typhimurium ( S. Typhimurium) is an important food-borne zoonotic pathogen that causes increased morbidity and mortality worldwide. The autotransporter (AT) proteins are a large and diverse family of extracellular proteins, many of which contribute to the pathogenicity of Gram-negative bacteria. The S. Typhimurium AT protein MisL mediates intestinal colonization in mice. Bioinformatics analyses indicated that MisL clusters with ATs are involved in bacterial biofilm formation, aggregation and adherence. In this study, we found that the misL overexpression increased S. Typhimurium biofilm formation. In addition, the misL deletion reduced bacterial adherence and invasion abilities on HeLa cells, but did not affect the bacterial virulence. Similarly, MisL expression in Escherichia coli strain promoted bacterial biofilm formation as well as adhesion and invasion capacities. However, the misL overexpression had no influence on the bacterial aggregation except for AAEC189Δflu, a strain lacking type I fimbriae. Moreover, we demonstrated that immunization with recombinant MisL protein stimulated the production of high IgG antibody titers, which conferred modest protection against S . Typhimurium infection. This study illustrates the novel biological functions and immunoprotective effects of MisL in S . Typhimurium. Abstract : Novel roles for the Salmonella autotransporter MisL.